Implementing Agri-Fishery Arts Education in Junior High School in Cabarroguis, Quirino Province - Cabanit, Ana Maria Mercedes; Peñalber, Martina (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the implementation of Agri-Fishery Arts (AFA) Education among junior high school students in Cabarroguis, Quirino Province, with the aim of determining students’ demographic characteristics, factors influencing their choice of AFA, challenges encountered, and the relationships among these variables. Anchored on Constructivist Learning Theory, Human Capital Theory, and the Input–Process–Output (IPO) Model, the study employed a descriptive–comparative–correlational research design. A total of 75 Grade 9 and Grade 10 students participated as respondents, and data were collected using a validated structured questionnaire covering demographic profile, influencing factors, challenges, and perceived outcomes. Descriptive statistics and inferential techniques, including t-test, one-way ANOVA, and Pearson r correlation, were used for analysis. The findings revealed that respondents were predominantly middle adolescents with balanced representation in sex and grade level and generally average to above-average academic performance. Students were primarily influenced to enroll in AFA due to its practical value, development of life and livelihood skills, self-reliance, and relevance to real-life and community needs, indicating strong intrinsic motivation. However, moderate challenges were identified, particularly in limited hands-on learning opportunities and inadequate facilities and resources. Significant differences were found when grouped according to age, sex, and grade level, while academic performance showed no significant effect. A significant positive relationship between age and influencing factors indicated that older students demonstrate greater appreciation for practical and career-oriented aspects of AFA. The study concludes that AFA is an inclusive and relevant program that supports learners’ practical skills and holistic development, but its effectiveness depends on improved instructional delivery and resource provision. It recommends strengthening experiential learning, enhancing facilities, and applying differentiated instruction. The study aligns with SDG 4 (Quality Education) by promoting competency-based learning and SDG 5 (Gender Equality) ensuring equal rights to economic resources and education. It also contributes to community and socio-economic sustainability by enhancing agricultural skills, workforce readiness, and local development in agricultural communities.
Keywords: Agri-Fishery Arts; agricultural education; demographic factors; experiential learning; student engagement; vocational education